The Signaling Role of Municipal Currencies in Local Development - Rajshri Jayaraman; Mandar Oak (Center for Economic Studies and ifo Institute (CESifo), 2003)
The last decade has seen the burgeoning of several hundred local community currency institutions in cities across the world. Although residents of these communities claim that local currency promotes local development, how if at all it does so has hitherto been unexplored. This paper argues that the introduction of a municipal currency may serve as a signal of demand for local goods. Where demand uncertainty deters firms from investing in more productive technologies, such a signal improves the chances that technology choice will be optimal. The introduction of a local currency therefore always improves ex-ante efficiency and may lead to ex-post efficiency, with strictly higher levels of productivity and welfare.
Keywords: 330